Code-switching: To what extent it benefits in EFL classroom? - Nurhamidah, Nurhamidah (English Language and Literature International Conference (ELLiC) Proceedings, 2018)
Bilingualism and multilingualism have been an issue in linguistics for decades and moreover the technology which shortens the distance between countries or even languages and evokes code-switching. Such phenomenon has been researched by many researchers and experts of linguistics to see what actually it functions. In EFL classroom, code-switching by some researchers has been considered as language barriers while others see code-switching as the communication strategy to ease the teaching-learning process. The two coined side are still developed and invited more creative researchers to reject or to support. Code-switching which commonly occurs in foreign language classroom is still under of unconscious state of both teachers and students to conduct. The code switching on this side will neglect based on the teachers and students who employ this in EFL classroom. This paper will be based on the literature study which have been mushrooming in the current state of code-switching.